Evaluation of the Implementation of the Procurement of Government Goods/Services In Gorontalo Regency - Pertiwi Kadir; Meimoon Ibrahim; Irwan Halid (Journal of Economic, Business, and Administration (JEBA), 2023)
ABSTRACT This study aims to: (1) determine and analyze the implementation of the government's procurement of goods/services in Gorontalo Regency. (2) To find out and analyze what factors influence the process of implementing government procurement of goods/services in Gorontalo Regency This research is a research with a qualitative descriptive approach, namely examining, analyzing and decrypting the data. The results showed that (1) the working group had carried out explanations, but the working group's readiness in providing initial explanations and in answering questions from participants was still not optimal, because there were still working groups that provided initial explanations that had passed the allotted time. (2) the evaluation of the bid documents has followed the existing regulations, however, due to frequent changes in regulations, the understanding of the working group may differ from one another. Because there are working groups that can quickly adjust existing regulations, some are not. (3) Proof of qualification is followed in accordance with existing regulations. It's just that the timeliness of the prospective provider is still lacking because it always comes at the time of proving the qualifications will end. (4) The stage of refutation of the working group tries to provide answers to potential providers in a good, relevant, and transparent manner. It's just that the bidders are dissatisfied. Because they didn't win, they use the rebuttal route to express their dissatisfaction. (5) Human resources and facilities and infrastructure are sufficient. However, if there are a large number of packages being tendered, the working group will ask for the assistance of personnel from other OPDs to become an election working group. (6) social, political and economic factors greatly influence the implementation of government procurement of goods/services. From an economic point of view, the tender process is the starting point for selecting business actors. Business actors will compete and will take advantage of existing resources and of course will increase the economic income of the community. Judging from the social conditions, the community can work or be directly involved in the project. If politics is very influential, but the working group must still be guided by the existing rules. So, there will be considerations that must be placed on the rules in the procurement of goods/services. (7) the disposition factor can affect the process of implementing government procurement of goods/services in the provider selection stage, it's just that the working group's attitude must always be able to understand the existing rules, so that everything can be adjusted